Reasoned administration and democratic legitimacy how administrative law supports democratic government - Mashaw, Jerry L. (Cambrdige, UK New York, NY Cambridge University Press, 2018)
"Preface and Acknowledgements Critiques of administrative governance go back at least to the Jeffersonian Republicans' objections to the creation of the First Bank of the United States. And, like those early "Democrats" laments, critical commentary is often focused on a presumed democratic deficit. For many, countering the pernicious effects of "big government", and re-establishing democracy and the rule of law, entails returning lawmaking to Congress and the judiciary. These complaints continue unabated in the academic literature, judicial decisions and popular political discourse. For example, conservative legalists have embraced Philip Hamburger's book, "Is Administrative Law Unlawful?" (answer yes) notwithstanding Hamburger's thoroughgoing misunderstanding of both modern American administrative law, and the functioning of seventeenth century royal prerogative to which Hamburger compared our modern administrative jurisprudence. No less than the Chief Justice of the U.S. Supreme Court has weighed in with his own concerns the Americans now live in a gigantic and all-powerful administrative state. As these words are written multiple bills are before Congress that would, among other things, make all significant agency regulations ineffective unless specifically approved by Congress and instruct reviewing courts to give agency interpretations of their organic statutes no deference upon judicial review"--
"Reasoned Administration and Democratic Legitimacy: How Administrative Law Supports Democratic Government explores the fundamental bases for the legitimacy of the modern administrative state. While some have argued that modern administrative states are a threat to liberty and at war with democratic governance, Jerry L. Mashaw demonstrates that in fact reasoned administration is more respectful of rights and equal citizenship and truer to democratic values than lawmaking by either courts or legislatures. His account features the law's demand for reason giving and reasonableness as the crucial criterion for the legality of administrative action. In an argument combining history, sociology, political theory and law, this book demonstrates how administrative law's demand for reasoned administration structures administrative decision-making, empowers actors within and outside the government, and supports a complex vision of democratic self-rule"--
Machine generated contents note: 1. Why reasons; 2. The rise of reason giving; 3. Reasons, reasonableness and accountability in American administrative law: the basic legal framework; 4. Reasonableness, accountability and the control of administrative policy; 5. Reasons, reasonableness and judicial review; 6. Reasons, administration and politics; 7. Reasoned administration and democratic legitimacy; 8. Reason and regret.
Includes bibliographical references and index.
Keywords: Administrative agencies -- United States; Administrative law -- United States; Administrative procedure -- United States; Democracy -- United States; Legitimacy of governments -- United States; Rule of law -- United States